A Multicenter Study on Mortality and Risk Factors in Patients with Acute Exacerbation of Cor Pulmonale in Plateau of China from 2012 to 2022 - Chenlu Yang; Qiang Zhang; Xiaofeng Ma; Haibo Dong; Yong Deng; Mingming Ma; Yuyan Wang; Shiya Zhu; Zhi Zhang; Junlin Gao; Yujuan Qi; Shuyan Han; et al. (Journal of Epidemiology and Global Health)
Abstract Background Cor pulmonale is common in plateau areas due to chronic hypoxia and pulmonary vascular remodeling. Yet, its mortality and related factors there are under researched. We aim to explore the mortality and related factors in patients with cor pulmonale at high altitudes. Methods This study is a multicenter follow-up study that included all patients with cor pulmonale from four hospitals in Qinghai Province from 2012 to 2022. Under gender stratification, the characteristics of patients with cor pulmonale were described based on survival status. A line chart was further drawn to depict the changing trend of the case fatality rate of patients with pulmonary heart disease with age. The dose-response relationship between the altitude of the patient’s residence and death was plotted using restricted cubic splines and presented based on ethnic stratification. Logistic regression was further used to explore the factors that affect the death of patients with cor pulmonale. Results The results showed that among 33,844 patients, a total of 1,451 died in the hospital, with a crude mortality rate of 4.3%. In the entire population and the Han subgroup, mortality risk initially rose with increasing altitude, then decreased, and rose again. In addition, age (odds ratio [OR]: 1.456, 95% confidence interval [CI]: 1.376–1.540), females (OR: 0.683, 95% CI: 0.609–0.764), residential altitude (OR 2000–2499 m: 1.510, 95% CI: 1.162–1.939; OR 2500–2999 m: 0.745, 95% CI: 0.562–0.988; OR≥ 3000 m 0.856 95% CI: 0.615–1.192) and ethnic group were associated with death among patients with cor pulmonale. Conclusion The mortality risk of cor pulmonale patients in high-altitude areas is closely related to altitude, and it is necessary to strengthen the control of poor prognosis in Han, elderly, high-altitude residents, and male pulmonary heart disease patients.